Regulatory Model for the Cancellation of Authentic Notarial Deeds Based on Principles of Justice - Mashdurohatun, Anis; Waruwu , Ingati Margaretha; Saktiawan , Muhammad Dias; Supriyadi, Supriyadi; Aaty El-Sonbaty, Atta Abdel (Lembaga Contrarius Indonesia, 2024)
The cancellation of an authentic notarial deed can be carried out by one of the parties or the aggrieved party if the deed contains legal defects, causing it to be downgraded to a private deed. The cancellation must be conducted by filing a lawsuit in the court with jurisdiction over the place where the authentic notarial deed was created. This research aims to analyze the cancellation of authentic notarial deeds from the perspective of civil procedural law, which is not yet based on the principles of justice. It also seeks to identify weaknesses in the current procedures and propose a justice-based reconstruction model for the cancellation of authentic deeds made by notaries. The study uses a socio-legal paradigm with relativism ontology and an empirical juridical approach, employing non-doctrinal legal research methods. Primary data were collected through field research, including interviews and/or questionnaires with competent parties. The findings reveal that the reasons for cancellation include non-fulfillment of objective conditions of agreements, absolute incapacity, lack of authority, contradictions with legal provisions, violations of public order or morality, fulfillment of legal events with void conditions, relative incapacity, defects of will, abuse of circumstances, breach of contract, and non-compliance with formal agreement requirements. The study suggests establishing a legal harmonization institution and including judicial decisions in the legislative hierarchy, as well as reconstructing the National Land Agency’s service system for better deed management.